Answer:
This question seems to be asking for the work, so I put it below.
Anyhow, Marla had 3.5 candies, and Ron had 10.5.
Explanation:
x = 3x - 7 (lets set this as "a") { a = 3x - 7}
x + 7 = 3x -7 + 7
x + 7 = 3x
( x + 7 ) / 3 = 3/3x
( x + 7 ) / 3 = x = *(same as "a") {a}
( x + 7 ) / 3 = 3x - 7
( x + 7 ) / 3 * 3 = ( 3x - 7 ) * 3
x + 7 = 9x - 21
x - x + 7 = 9x - x - 21
7 = 8x - 21
7 + 21 = 8x - 21 + 21
28 = 8x
28 / 8 = 8/8x
3.5 = x
We can plug this back into the original equation and find that it is correct because:
x = 3x - 7
x = 3.5 =====
3.5 = 3( 3.5 ) - 7
3.5 = 10.5 - 7
3.5 = 3.5